Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2011
DOI: 10.1145/1978942.1979248
|View full text |Cite
|
Sign up to set email alerts
|

User-centred multimodal reminders for assistive living

Abstract: While there has been a lot of research on the usability of reminders and alarms in the work context, the home has been somewhat neglected despite the importance of reminder systems for telecare and assistive living systems. We conducted a comprehensive mixed-methods study into the requirements for useable and acceptable reminders in the home. The study consisted of a questionnaire (N=379), 6 focus groups, and 7 home tour interviews. Our results highlight the need for highly flexible and contextualized multimod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
97
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 17 publications
(21 reference statements)
0
97
0
Order By: Relevance
“…Providing multiple ways to interact can improve accessibility, which has prompted a number of researchers to call for the inclusion of multiple modalities in home care technology [11,19,25]. In addition, researchers have argued that dynamically switching between modalities when appropriate will also lead to increased user acceptability [1,18,30,31]; for example, switching to a more private modality (e.g.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Providing multiple ways to interact can improve accessibility, which has prompted a number of researchers to call for the inclusion of multiple modalities in home care technology [11,19,25]. In addition, researchers have argued that dynamically switching between modalities when appropriate will also lead to increased user acceptability [1,18,30,31]; for example, switching to a more private modality (e.g.…”
Section: Related Workmentioning
confidence: 99%
“…There have been numerous attempts at creating a model of when to deliver notifications in the home. Vastenburg, Keyson & Ridder [27] argued that user acceptance of a notification is dependent on the message urgency and the attentional focus of the user, but did not take into account user activity or social context, which other researchers have argued is very important in the home [18,19,24]. Nagel, Hudson & Abowd [24] found that people had different opinions on which activities could be acceptably interrupted.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations